436. DIFFERENCES IN MULTIDISCIPLINARY TEAM ASSESSMENT ON ESOPHAGEAL CANCER PATIENTS IN SWEDEN—A MULTICENTRE STUDY. (24th September 2022) - Hannan, Christine Jestin; Risso, Solange León; Lindblad, Mats; Szabo, Eva; Edholm, David; Bartholomä, Wolf Claus; Åkesson, Oscar; Lindberg, Fredrik; Strandberg, Sara; Linder, Gustav; Hedberg, Jakob
Abstract: There are differences in esophageal cancer care across different counties in Sweden. According to national guidelines, all patients should be offered equal care which should be administrated by regional multidisciplinary cancer conferences (MCCs). The aim of the study was to investigate differences between the six regional MCCs in Sweden regarding clinical stageing and recommended treatment. Ten consecutive cases per participating center, 60 cases in total, were planned for inclusion. After anonymization the radiological investigations were presented, along with the original case-specific medical history, anew at the six regional MCCs. Estimation of clinical TNM and treatment allocation (curative, palliative or best supportive care) were compared between MCCs as well as with the original assessment. Interim analysis was performed in April 2022 when ten cases had been presented at five of the six regional MCCs. All available cases were assessed at five MCCs in addition to the previous original assessment (60 assessments). The mean age for the first ten cases was 74.8 years (SD ± 9.8 years). Eight out of ten cases were men. In estimations of T- and N-stage the MCCs agreed in only one out of ten cases. In half of the cases more than three different estimations of N-stage were made. For clinical M-stage there was exact agreement in three cases. In determination of recommended treatment, all five MCCs were in agreement on half of the cases. Preliminary data show striking differences, both in assessment of TNM as well as treatment recommendation at different MCCs. One patient, recommended curative treatment by one MCC could be allocated to palliative care by another. Inclusion is ongoing and further analysis of these differences are warranted to achieve more equal care for esophageal cancer patients in Sweden. MCC_fig1.jpg (could not be inserted).